Efektivitas Pengelolaan Bank Sampah Studi Kasus Bank Sampah Hatim Berseri - Restu, Danuanda; Tia Wardani, Farra; Amelia, Riniata (Ri'ayah: Jurnal Sosial dan Keagamaan, 2025)
This study examines the effectiveness of waste management by the Hatim Berseri Waste Bank, the factors influencing it, and the impacts resulting from effective waste management, both on the environment and the economy. Population growth can lead to an increase in waste volume, making the role of waste banks as community-based waste management crucial. This study is based on field research using a qualitative method approach. Data were obtained by observing the waste bank being studied, namely the Hatim Berseri Waste Bank. Researchers conducted interviews with the managers of the Hatim Berseri Waste Bank and the surrounding community to gather the necessary information. In addition, researchers also collected documents related to waste bank management. Secondary data were obtained from research results, journals, or other relevant reference sources. From the results of the research that has been conducted, it can be concluded that the waste management activities by the Hatim Berseri Waste Bank have been running quite effectively. However, there are several aspects that can be further improved in waste management by the Hatim Berseri Waste Bank, namely related to the level of community participation, so that other aspects such as the level of waste volume reduction and the environmental and economic impacts received by the community can be more optimal.